Generation and Characterization of Mouse Models of C3 Glomerulonephritis With CFI D288G and P467S Mutations - Song, Hui; Zhang, Mingchao; Li, Xue; Xu, Feng; Zhang, Difei; Zhu, Xiaodong; Zhang, Jiong; Qin, Weisong; Shi, Shaolin; Wen, Jiqiu (Frontiers in Physiology, 2021)
C3 glomerulopathy (C3GP) is a disease entity caused by abnormality of the complement alternative pathway (AP) and characterized by C3 deposition in glomeruli. Many variations or mutations of complement factors are believed to underlie the susceptibility to C3GP, but there is a lack of experimental evidence. We have recently reported a patient with C3 glomerulonephritis (C3GN) and compound heterozygosity of two novel variations in the complement factor (CFI). Here, we generated a mouse model to mimic the CFI variations for studying pathogenicity of CFI variations in C3GN development. We used CRISPR/Cas9 system to make mutant mouse lines that carried D288G and P467S mutations in CFI, respectively, and crossed them to generate mice with compound heterozygosity of CFI D288G and P467S. The mice were all normal in either SPF (specific pathogen free) or regular environment. When treated with lipopolysaccharides (LPS), a bacterial endotoxin that mimics infection and sepsis, the mice developed albuminuria, kidney function impairment, and C3 glomerular deposition at levels comparable with the wild-type mice. The mice with other genotypes concerning CFI D288G and P467S were also tested in parallel. Unexpectedly, we found that the D288G homozygotes all developed severe mesangial deposition of C3 in the LPS model, indicating that CFI D288G variation was involved in the C3 deposition, a key feature of C3GN. The mouse lines generated in the present study can be used to further study the role of CFI variations in C3GN development; in addition, they may be used to screen and test infections and environmental factors capable of triggering C3GN.